Determining the incidence of heart malformations in neonates: A novel and clinically approved solution - Bordbar, Arash; Kashaki, Mandana; Vafapour, Maryam; Sepehri, Amir A. (Frontiers in Pediatrics, 2023)
Background: Screening for congenital heart malformation should be done as early as possible and is essential to save lives and reduce the incidence of undetected adult congenital heart diseases. Over 50% of neonates with heart malformations remain unrecognized at birth. Accurate screening for congenital heart malformations is achievable using a certified and internationally patented digital intelligent phonocardiography machine. This study aimed to assess the actual incidence of newborn heart defects in a well-baby nursery and evaluate digital intelligent phonocardiogram screening for critical congenital heart defects. Methods: We conducted the “Neonates Cardiac Monitoring Research Project” (ethics approval number: IR-IUMS-FMD. REC.1398.098) at the Shahid Akbarabadi Maternity Hospital. This study is a retrospective analysis of screening congenital heart malformation in 840 neonates. Randomly, 840 neonates from the well-baby nursery underwent standard clinical examinations at birth and digital intelligent phonocardiogram examination in a double-blinded format. A pediatric cardiologist performed echocardiography for each neonate classified as abnormal using the intelligent machine or routine medical examinations. If a follow up was demanded by the pediatric cardiologist, the neonate was considered as having a congenital heart malformation and the cumulative incidence proportion was calculated accordingly. Results: The incidence of heart malformations in the well-baby nursery was 5%, and 44% of neonates with heart malformations were unrecognized at birth based on the standard medical examination results, including those with critical congenital heart defects (CCHD). An intelligent phonocardiogram recognized 100% of neonates with heart malformations. Conclusion: We accurately and cost-effectively screened for congenital heart malformations in all neonates in our hospital using a digital intelligent phonocardiogram. We detected neonates with CCHD and congenital heart defects using an intelligent machine; these could not be detected using standard medical examinations. In addition, the intelligent machine interpreted innocent murmurs as healthy heart sounds.